FOXM1 induces a global methylation signature that mimics the cancer epigenome in head and neck squamous cell carcinoma. - Muy-Teck Teh; Emilios Gemenetzidis; Deeviyaben Patel; Rameez Tariq; Ayesha Nadir; Adiam W Bahta; Ahmad Waseem; Iain L Hutchison (PLoS ONE, 2012)
The oncogene FOXM1 has been implicated in all major types of human cancer. We recently showed that aberrant FOXM1 expression causes stem cell compartment expansion resulting in the initiation of hyperplasia. We have previously shown that FOXM1 regulates HELLS, a SNF2/helicase involved in DNA methylation, implicating FOXM1 in epigenetic regulation. Here, we have demonstrated using primary normal human oral keratinocytes (NOK) that upregulation of FOXM1 suppressed the tumour suppressor gene p16(INK4A) (CDKN2A) through promoter hypermethylation. Knockdown of HELLS using siRNA re-activated the mRNA expression of p16(INK4A) and concomitant downregulation of two DNA methyltransferases DNMT1 and DNMT3B. The dose-dependent upregulation of endogenous FOXM1 (isoform B) expression during tumour progression across a panel of normal primary NOK strains (n = 8), dysplasias (n = 5) and head and neck squamous cell carcinoma (HNSCC) cell lines (n = 11) correlated positively with endogenous expressions of HELLS, BMI1, DNMT1 and DNMT3B and negatively with p16(INK4A) and involucrin. Bisulfite modification and methylation-specific promoter analysis using absolute quantitative PCR (MS-qPCR) showed that upregulation of FOXM1 significantly induced p16(INK4A) promoter hypermethylation (10-fold, P<0.05) in primary NOK cells. Using a non-bias genome-wide promoter methylation microarray profiling method, we revealed that aberrant FOXM1 expression in primary NOK induced a global hypomethylation pattern similar to that found in an HNSCC (SCC15) cell line. Following validation experiments using absolute qPCR, we have identified a set of differentially methylated genes, found to be inversely correlated with in vivo mRNA expression levels of clinical HNSCC tumour biopsy samples. This study provided the first evidence, using primary normal human cells and tumour tissues, that aberrant upregulation of FOXM1 orchestrated a DNA methylation signature that mimics the cancer methylome landscape, from which we have identified a unique FOXM1-induced epigenetic signature which may have clinical translational potentials as biomarkers for early cancer screening, diagnostic and/or therapeutic interventions.